Impact of us Stock Market and Oil Price on Bric Stock Markets and their Interdependency - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Globalization leads financial market of one country to become more integrated with other countries. In this environment the knowledge of dependency between the stock market helps the investors and portfolio managers for international investment and diversification. This paper investigates the linkage among BRIC market indices, i.e. Brazil, Russia, India and China, and their relation with US market and oil price. Restricted Vector Auto Regression (VAR) model is employed to gauge the interdependencies among the selected stock market and the short-term relationship is tested with the help of Granger causality test by using the daily data from 2 nd January 1998 to 30 th September 2014. Based on the result of Final prediction error (FPE) and Akaike information criterion (AIC) six lag lengths is selected as the optimal lag for the VAR model. The results of VAR model indicate that the return of Brazil, Russia and India having co-movement with US market and oil price. However, China does not exhibit the co-movement with US stock market but it does with oil price. Brazil market causes more other market than is caused by them, China and Russia Granger-cause each other. However, to the lesser extent, India Granger-cause China and Russian market. Us market has high significant positive influence than the oil price on Brazil, Russia and India. On the other hand, Oil price has significantly positive influence on China where as US market not influences the Chinese market.